2018
DOI: 10.21560/spcd.v18i39974.451063
|View full text |Cite
|
Sign up to set email alerts
|

Yabanci Düşmanliği (Zenofobi̇) Ölçeği̇ni̇n Türk Kültürüne Uyarlanmasi: Geçerli̇k Ve Güveni̇rli̇k Çalişmasi

Abstract: Amaç: Bu çalışma, Yabancı Düşmanlığı (Zenofobi) Ölçeği (YDÖ)'nin geçerlik ve güvenirlik bakımından incelenerek Türkçeye uyarlanması amacı ile yürütülmüştür. Yöntem: Çalışmanın örneklemini Türkiye'nin farklı illerinde yaşayan, araştırmaya katılmayı gönüllü olarak kabul eden 18 ve daha büyük yaştaki 586 kadın ve erkek oluşturmaktadır. Yabancı Düşmanlığı (Zenofobi) Ölçeği Türkçe formunda 11 madde vardır. Ölçeğin güvenirliğini belirlemek için Cronbach Alfa iç tutarlık katsayısı hesaplanmış, madde ayırt edicilikler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…Ölçek puanı arttıkça yabancı düşmanlığı tutumu artmaktadır. Ölçeğin güvenirlik katsayısı olan Cronbach Alfa değeri 0,87 olarak hesaplanmıştır (22). Çalışmamızda ise Cronbach's alpha katsayısı 0.92 olarak bulundu.…”
Section: Yabancı Düşmanlığı öLçeğiunclassified
“…Ölçek puanı arttıkça yabancı düşmanlığı tutumu artmaktadır. Ölçeğin güvenirlik katsayısı olan Cronbach Alfa değeri 0,87 olarak hesaplanmıştır (22). Çalışmamızda ise Cronbach's alpha katsayısı 0.92 olarak bulundu.…”
Section: Yabancı Düşmanlığı öLçeğiunclassified
“…The lowest score that can be obtained from the scale is 11, the highest score is 66, and a higher score means that the risk of xenophobia increases. In Ozmete et al study, Cronbach’s alpha value was found .87 (Özmete et al, 2018). In our study, Cronbach’s alpha value was found .87.…”
Section: Methodsmentioning
confidence: 90%
“…The Original Xenophobia Scale consists of 14 items (Van Der Veer et al, 2011). The Turkish adaptation was made by Ozmete et al (Özmete et al, 2018). In the adaptation study to Turkish, the Xenophobia Scale consists of 11 items and a single factor structure.…”
Section: Methodsmentioning
confidence: 99%
“…384 young people aged between 15-32 years participated in the study. A personal information form and a "Xenophobia Scale" developed by Van Der Veer, Ommundsen, Yakushko&Higler (2011) and adapted into Turkish by Özmete, Yıldırım and Duru (2018) were utilized in the study. The predictive power of independent variables was calculated by binary logistic regression analysis.…”
Section: Structuredabstractmentioning
confidence: 99%